Hungarian Development Opportunities of the Resilient and Innovative Space Industry - Parragh, Bianka; Báger, Gusztáv; Kovács, Árpád; Tóth, Gergely (Public Finance Quarterly, 2021)
This study was motivated by the fact that space industry has become one of the most innovative, rapidly developing, least crisis-sensitive industries, which grows dynamically worldwide. Its resilience to shocks is quite apparent. Since the outbreak of the pandemic1 in spring 2020, the sector preserved many jobs and created new ones, while its innovative and technological advances remained uninterrupted. This study – based on surveys, statistical and other databases – aims to take stock of the current state of the Hungarian space sector and industry, and to set out possible directions for state involvement to enhance further progress. Our research confirmed that the Hungarian space industry, although its direct contribution to social performance is moderate today, employs a significant number of highly skilled workers and introduces cuttingedge technologies. Furthermore, through its innovations and technological and scientific transfers, its contribution to the competitiveness of the Hungarian economy is significant, even at the current level of its capacities. With adequate support and wise investments, the added value, the growth and international potential and the global space industry value chain involvement the space industry can be exploited to a much greater extent than at present.